ShenQiGan Extract Repairs Intestinal Barrier in Weaning-Stressed Piglets by Modulating Inflammatory Factors, Immunoglobulins, and Short-Chain Fatty Acids - Rongxia Guo; Chenghui Jiang; Yanlong Niu; Chun Niu; Baoxia Chen; Ziwen Yuan; Yongli Hua; Yanming Wei (Animals)
Weaning stress damages the intestines and disrupts the intestinal barrier in piglets, which significantly impacts the pig farming industry’s economy. We aimed to examine the effects of ShenQiGan extract (CAG) on intestinal barrier function and explore the underlying molecular mechanisms in stress-challenged weaned piglets. The experimental design involved 80 weaned piglets aged 28 days (with an average body weight of 7.78 ± 0.074 kg) that were randomly allocated into four groups: Control, LCAG (0.1% CAG), MCAG (0.5% CAG), and HCAG (1.0% CAG). After a 28-day trial period, the growth performance and incidence of diarrhea in piglets were evaluated. CAG increased the average daily gain of weaned piglets, reduced the feed-to-gain ratio, and decreased the incidence of diarrhea. It significantly lowered serum inflammatory cytokine levels while elevating immunoglobulin levels. The supplement notably enhanced concentrations of acetic acid, propionic acid, butyric acid, and isobutyric acid. Furthermore, CAG demonstrated intestinal morphology restoration and upregulation of tight junction proteins and MUC2 protein expression in jejunum. At the mRNA level, it significantly upregulated the expression of Occludin, Claudin1, and MUC2 genes. CAG improves growth performance and mitigates diarrhea in weaned piglets by enhancing intestinal barrier integrity, modulating systemic inflammatory responses, elevating immunoglobulin levels, and promoting short-chain fatty acids (SCFAs) production in the cecum.